Effect of the grip angle on off-spin bowling performance parameters, analysed with a smart cricket ball - Fuss, F.K.; Doljin, B.; Ferdinands, R.E.D. (Proceedings, 2018)
In the off-spin bowling grip, the ball is clamped between index and middle fingers. Spin bowlers attempt to select a spread angle between these two fingers that achieves comfort and optimises performance. The aim of this paper was to investigate whether the standard grip is superior to narrow and wide grips. The bowling performance parameters were obtained from a smart cricket ball. Smart ball data revealed that the performance parameters varied with grip type. The following parameters were optimum at the standard grip: spin rate, resultant torque, spin torque, peak angular acceleration, and peak power. The following parameters were optimum at standard and wide grips: efficiency. The following parameters were optimum at standard and narrow grips: pitch angle of spin axis. The following parameters were optimum at the wide grip: precession and the precession torque. In general, the data tended to show that the standard grip is most effective for spin bowling. However, more research is needed to confirm this result, because the precession and precession torque were optimum at the wide grip, suggesting that this may have a superior performance over the standard and narrow grips.